Respuesta :
2n - 3 = 9
If you are solving for n:
Isolate it by doing the opposite of PEMDAS; Also, what you do to one side you do to the other (because of the equal sign)
2n - 3 = 9
2n - 3 (+3) = 9 (+3)
2n = 12
2n/2 = 12/2
n = 6
n = 6 is your answer
hope this helps
If you are solving for n:
Isolate it by doing the opposite of PEMDAS; Also, what you do to one side you do to the other (because of the equal sign)
2n - 3 = 9
2n - 3 (+3) = 9 (+3)
2n = 12
2n/2 = 12/2
n = 6
n = 6 is your answer
hope this helps
2n-3=9
------------
Add 3 to each side
2n−3+3=9+3
2n = 12
------------------
Divide each side by 2
2n ÷ 2 = 12 ÷ 2
n = 6
------------
Add 3 to each side
2n−3+3=9+3
2n = 12
------------------
Divide each side by 2
2n ÷ 2 = 12 ÷ 2
n = 6